1995
DOI: 10.1128/jcm.33.8.2107-2113.1995
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to detect and identify Bartonella species in routine clinical laboratory yields Bartonella henselae from human immunodeficiency virus-positive patient and unique Bartonella strain from his cat

Abstract: We wished to develop a cost-effective, rapid strategy to detect and identify Bartonella species in the clinical laboratory and to determine the prevalence of Bartonella infection in the Houston veteran population. Bartonella colonies were identified by colony morphology, Gram stain, RapID ANA, repetitive extragenic palindromic-PCR (REP-PCR) and whole-cell fatty acid (CFA) analysis, and these methods were compared for their usefulness. A new test order for ''Rochalimaea culture'' (the genus Bartonella was previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 30 publications
3
46
1
3
Order By: Relevance
“…CFA analysis is useful in identifying members of the Bartonella genus, but it could not discriminate between B. henselae and B. quintana. The CFA patterns found in the present study are similar to those published previously (1,12,15,16). Identification of the Bartonella species was done by 16S rRNA gene sequencing, SDS-PAGE, and ERIC-PCR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…CFA analysis is useful in identifying members of the Bartonella genus, but it could not discriminate between B. henselae and B. quintana. The CFA patterns found in the present study are similar to those published previously (1,12,15,16). Identification of the Bartonella species was done by 16S rRNA gene sequencing, SDS-PAGE, and ERIC-PCR.…”
Section: Discussionsupporting
confidence: 89%
“…Biochemical tests have been reported to be nondiscriminatory for Bartonella species (1,15). The results obtained with the RapID ANA II system differed from those of Welch et al (15) and agreed with those of Clarridge et al (1), who found identical profiles for B. henselae and B. quintana. We isolated a Corynebacterium species from two cats.…”
Section: Discussionsupporting
confidence: 60%
“…Rather most of the transmission we infer requires the transmission of Bartonella into a domestic or peridomestic animal, which can then transmit it to the human. Despite the noted host specificity of Bartonella (Table S1), the diversity of strains that infect humans and their distribution across the phylogenetic tree of Bartonella suggests that this bacterial genus can and will switch hosts when given the opportunity (especially when hosts are immunocompromised [29, 30]). The relative evolutionary lability of these genotypes is further underscored by the instances in the global phylogeny of genotypes being exchanged between bats and rodents (at least five times).…”
Section: Discussionmentioning
confidence: 99%
“…Bartonella clarridgeiae was first isolated in the USA from the pet cat of a HIV-positive patient (Clarridge et al 1995). This Bartonella species has been less frequently isolated from domestic cats than B. henselae, as it appears to be more difficult to isolate on conventional 5% blood agar plates and is unevenly distributed in cat populations worldwide .…”
Section: Bartonella Clarridgeiaementioning
confidence: 99%